MEMAHAMI KONSEP DASAR KURIKULUM PENDIDIKAN ISLAM - Muhammad Cikal Hanafi; Indi Rahmawati, Roza Yulyastri Koto, Gusmaneli (CV. ADIBA AISHA AMIRA, 2024)
This discussion explores key concepts in the Islamic Curriculum and classifies science concepts in the Islamic context. The Islamic curriculum is guided by Islamic values and teachings, providing a foundation for individual development in a Muslim society. The focus of this article includes teaching the Koran, hadith, Islamic ethics, and the integration of moral values in the learning process. In addition, the classification of knowledge concepts in Islam is also outlined, identifying traditional scientific disciplines such as religious knowledge, science, and social sciences that form the foundation of Islamic education. This approach not only considers theological aspects, but also describes the relationship between science and everyday life. Discussions regarding the relationship between modern and traditional science from an Islamic perspective are also a focus. By detailing these concepts, this article aims to provide a deeper understanding of the essence of the Islamic Curriculum and the scientific foundations that form the foundation for the formation of individual Muslim thought and character. Through exploring these concepts, it is hoped that we can provide a holistic view to improve the quality of Islamic education at various levels.